Changes to commute mode: The role of life events, spatial context and environmental attitude. (July 2016) - Clark, Ben; Chatterjee, Kiron; Melia, Steve
Highlights: National panel survey analysis of commute mode changes year to year. 20 per cent of English employees changed commute mode from one year to the next. Mode switches occur when commute distance changes (with change of home or job). Pro-environmental attitude precedes switches away from car commuting. Good public transport and mixed land use encourage switches away from car commuting. Abstract: It has been suggested that commuting behaviours become habitual and that changes to commute mode are more likely at the time of major life events. However, evidence to support this has so far been limited to analyses of small-scale samples. To address this evidence gap, we use two waves of panel data from the UK Household Longitudinal Study (2009/10 and 2010/11) to identify and explain the prevalence of individual change in commute mode from year to year amongst a representative sample of the English working population ( n  = 15, 200). One third of those that cycle or get the bus to work, and one quarter of those that walk to work, are shown to change commuting mode by the following year. Car commuting is more stable, with only one in ten car commuters changing mode by the following year. Commute mode changes are found to be primarily driven by alterations to the distance to work which occur in association with changing job or moving home. Switching to non-car commuting becomes much more likely (9.2 times) as the distance to work drops below three miles. High quality public transport links to employment centres are shown to encourage switches away from car commuting and mixed land uses are shown to encourage switches to active commuting (walking and cycling). Switches away from car commuting are found to be more likely (1.3 times) for those with a pro-environmental attitude. The attitude orientation is shown to precede the behaviour change, demonstrating evidence of 'cause and effect'. Overall, the study shows that changes in commuting behaviour are strongly influenced by life events, spatial context and environmental attitude.